A meta-Ethnography on Parents' Experiences of the Internet As a Source of Health Information - Thale Strand; Thomas Westergren (SAGE Publishing, 2024)
The Internet is increasingly being used as a health information resource. This meta-ethnography aimed to synthesize the literature on how parents of children aged below 5 years' experienced using the Internet for health information purposes. We employed an interpretive meta-synthesis approach-meta-ethnography-according to Noblit & Hare's seven phases. A total of 22 articles met the inclusion criteria, representing four continents and with 650 participants, mainly mothers. We analysed and synthesized the primary studies into the following lines-of-argument synthesis representing a novel conceptual understanding of the phenomenon: Parents experience the Internet as "A cyber partner for child caring" being a 24/7 available "go-to" among other confined sources. Parents find ways of "patching together" trustworthy information in solicitude for their child's health while navigating between trust and anxiety. They relate online and share their experiences and secrets without being rejected. Clinicians and parents may benefit from "partnering" with this resource.